Assessment of Clinical Learning and Training Environment for Maternal and Child Health Nursing Students - hasan, rajaa; abbas, iqbal (Iraqi National Journal of Nursing Specialties, 2014)
Objective: To assess the clinical learning environment and clinical training for students’ in maternal and child health nursing. Methodology: A descriptive study was conducted on non probability sample (purposive) of (175) students’ in Nursing College/ University of Baghdad for the period of June 19th to July 18th 2013. A questionnaire was used as a tool of data collection to fulfill with objective of the study and consisted of three parts, including demographic, clinical learning environment and clinical training for students’ in maternal and child health nursing. Descriptive statistical analyses were used to analyze the data. Results: The results of the study revealed that the 65.1% of student at age which ranged between (19-23) years and 56% were male student, 66.9% were third year nursing students, and 59.4% were morning study. The study revealed that there were high mean score response among study sample except item (11) the response was (No) in which as (The learning environment in the hospital with a homogeneous environment college) at student’s attitude’s regarding clinical learning environment. And the study revealed that there were high mean score response among study sample at the clinical training. Recommendations: The study recommended to need to conduct other the researches to evaluate the actual clinical learning environment for nurse’s skills and practices performance in the hospital. And to determine factors influence student’s during clinical learning environment and clinical training